Analisis Ketidakmerataan Cakupan Jaringan 5G di Pulau Jawa Berdasarkan Distribusi Infrastruktur gNodeB - Faliza Martina Ambadar; Panji Bati Asmara; Dwiki Mohamad Rifki; Rustamaji Rustamaji (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
Fifth Generation (5G) New Radio (NR) technology has become a crucial element in the digitalization process in Indonesia, with the initial phase focused on Java Island as the country's main economic region. This study explores the gap in 5G network coverage on Java Island through an analysis of gNodeB infrastructure distribution using descriptive quantitative methods and spatial analysis. The findings indicate that although Java dominates approximately 67.6% of the country's 5G infrastructure, its distribution remains highly uneven. DKI Jakarta achieves almost complete coverage, while West Java, Central Java, and East Java only record coverage rates below 15%, which is limited to metropolitan areas. Technical aspects such as the dominance of the 2.3 GHz mid-band spectrum, low gNodeB density, and the adoption of Non-Standalone (NSA) architecture are the causes of poor coverage and service quality, with throughput ranging from 200–400 Mbps and latency between 20–30 ms. This situation highlights the digital divide on the island of Java, where regencies and sub-urban areas are still lagging far behind. In order to support equitable and inclusive digitalization, a strategy for equal distribution is needed, including multi-band spectrum allocation, accelerating the transition to Standalone (SA) architecture, and developing more equitable infrastructure outside metropolitan centers.